1994
DOI: 10.2307/3870006
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Is Not the Translocated Signal Responsible for Inducing Systemic Acquired Resistance but Is Required in Signal Transduction

Abstract: Infection of plants by necrotizing pathogens can induce broad-spectrum resistance to subsequent pathogen infection. This systemic acquired resistance (SAR) is thought to be triggered by a vascular-mobile signal that moves throughout the plant from the infected leaves. A considerable amount of evidence suggests that salicylic acid (SA) is involved in the induction of SAR. Because SA is found in phloem exudate of infected cucumber and tobacco plants, it has been proposed as a candidate for the translocated signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
131
0
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(144 citation statements)
references
References 19 publications
(43 reference statements)
9
131
0
4
Order By: Relevance
“…Most recently, independent experiments have been conducted showing also that the concept of elevated levels of H202 [9] as a consequence of possible catalase inhibition by SA is not required for systemic acquired resistance [23] and that H202 does not function downstream of SA in the induction of PR protein expression [24]. Furthermore, it has previously been shown that SA is essential for the development of systemic asquired resistance [25] but that the systemic acquired resistance inducing signal is not SA [26].…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, independent experiments have been conducted showing also that the concept of elevated levels of H202 [9] as a consequence of possible catalase inhibition by SA is not required for systemic acquired resistance [23] and that H202 does not function downstream of SA in the induction of PR protein expression [24]. Furthermore, it has previously been shown that SA is essential for the development of systemic asquired resistance [25] but that the systemic acquired resistance inducing signal is not SA [26].…”
Section: Discussionmentioning
confidence: 99%
“…SA was suggested as an endogenous signal substance in this process (Malamy et al, 1990;Metraux et al, 1990;Rasmussen et al, 1991;Yalpani et al, 1991;Raskin, 1992), and recent reports corroborated the local requirement of SA at the site of the challenge inoculation (Gaffney et al, 1993). However, grafting experiments with transgenic tobacco conceivably ruled out SA as the mobile signal for SAR transmission, and its exact role is still under controversial discussion (Vernooij et al, 1994;Shulaev et al, 1995).…”
mentioning
confidence: 99%
“…glucanase and chitinase, was correlated with the SAR in remote tissues (Binder et al, 1989). Although the experimental proof is still lacking for major crop plants, the application of the SAR concept for crop protection is appealing, and chemicals like INA or BTH, which mimic the action of SA and trigger the SAR response at micromolar concentrations in cucumber, tobacco, or Arabidopsis Kessmann et al, 1994;Friedrich et al, 1996;Lawton et al, 1996) were developed commercially. Plants sprayed with these chemicals revealed no signs of metabolic changes unless inoculated subsequently with a fungus.…”
mentioning
confidence: 99%
“…The constitutive expression of salicylate hydroxylase, encoded by the nahG gene from Pseudomonas putida, prevented the accumulation of SA in transgenic tobacco by converting it to catechol, which is inactive in SAR. Treatment of nahG plants with tobacco mosaic virus did not induce SAR (9) or SAR gene expression in systemic leaves (10). Grafting experiments involving nahG and wild-type tobacco have suggested that although SA is probably not a long distance signal, its presence in systemic tissue is absolutely required for PR protein expression and establishment of SAR (10).…”
mentioning
confidence: 99%
“…Treatment of nahG plants with tobacco mosaic virus did not induce SAR (9) or SAR gene expression in systemic leaves (10). Grafting experiments involving nahG and wild-type tobacco have suggested that although SA is probably not a long distance signal, its presence in systemic tissue is absolutely required for PR protein expression and establishment of SAR (10). PR-1a gene expression in infected tissues is dependent on SA accumulation and supports the suggestion that at least local induction of this PR protein operates via salicylate signaling (11).…”
mentioning
confidence: 99%